Developing Services for the Wireless Internet - Morisio, Maurizio; Torchiano, Marco; SpringerLink (Online service) (London : Springer London, 2006)
Accessing Internet services and applications through mobile wireless devices is already a reality for some people, and is just around the corner for most others. However, the success of the wireless Internet has to be fuelled by the availability of wireless-specific data services and applications in order to fully exploit its business potential and to provide actual return on investment. This book is for developers of wireless Internet services. It addresses the technical issues that can get in the way of the production of a successful service: variability of terminals, unstable technology, incomplete testing environment, variable bandwidth and quality of service. Useful techniques and methods when handing these issues are proposed using two case studies: a mobile game and a mobile trading service. Dr. Maurizio Morisio is associate professor of Software Engineering at Politecnico di Torino, Italy. Dr. Marco Torchiano is assistant professor at Politecnico di Torino, Italy.
Software Development Processes -- Technology -- Software Architecture of Wireless Services -- WISE Experience Pearls -- Pilot Projects.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering; Information Systems Applications (incl. Internet).; Electronic books